Analysis of Land Value Distribution in East Jakarta with a Spatial Modeling Approach - Ester Ulina Suranta Perangin Angin; Chotib Chotib; Irene Sondang (Eduvest - Journal of Universal Studies, 2025)
This study aims to analyze the distribution of land value in the Administrative City of East Jakarta through spatial modeling. With the increasing concentration of economic activities in East Jakarta, the demand for land also continues to increase, which has an impact on the increase in land values in the area. This study uses market data and Tax Object Selling Value (NJOP) from 1,522 land sample points, with variables that affect land value, such as land area, building area, and distance to the village and sub-district administrative centers. The spatial analysis approach with the Geoda application is used to evaluate spatial dependencies through the Classic, Spatial Lag, and Spatial Error models. The results of the study show that the variables of building area and distance to the village have a significant influence on market prices and NJOP in East Jakarta. The spatial dependency test carried out by the Lagrange Multiplier (LM) Lag and LM Error methods indicated the existence of spatial autocorrelation in the dependent variables. In addition, the results of the Moran's I and LISA indices identified areas with high (hot spots) and low (cold spots) value patterns, which describe the spatial distribution of land values in the region. This research is expected to contribute to spatial planning and property tax policy. By understanding the factors that affect land value, the government and property developers can make more effective decisions in the management of urban areas of East Jakarta.